Beetles as Plant Pathogen Vectors - Wielkopolan, Beata; Jakubowska, Magdalena; Obrępalska-Stęplowska, Aleksandra (Frontiers in Plant Science, 2021)
Herbivorous insects, likewise, other organisms, are exposed to diverse communities of microbes from the surrounding environment. Insects and associated with them microorganisms share a range of relationships, including symbiotic and pathogenic. Insects damage plants by feeding on them and delivering plant pathogens to wounded places, from where pathogens spread over the plant. Thus insects can be considered as both, pests and reservoirs or vectors of plant pathogens. Although beetles are not mentioned in the first place as disease vectors, their transmission of pathogens also takes place and affects the ecosystem. Here we present an overview of beetles as vectors of plant pathogens, including viruses, bacteria, fungi, nematodes, and Oomycota, which are responsible for developing plant diseases that can have a significant impact on crop yield and quality.